(untitled) (Iranian Journal of Kidney Diseases, 2020)
Introduction. There is a mutual relationship between hypertension and renal failure, so that hypertension can be considered as a common finding in patients with end-stage renal disorders. Patients with persistent hypertension despite multiple medications are at high risk for adverse cardiovascular and kidney events. Some studies suggest that there is a correlation between RI and renal function in kidney diseases. Therefore, we conducted a study to investigate the relationship between renal arterial resistive index (RRI) and renal outcomes in patients with resistant hypertension. Methods. This 2-years cross-sectional study was performed on patients with resistant hypertension. All patients undergo GFR, serum Cr and urine Alb tests. Then Doppler ultrasound was performed by a radiologist to measure RRI and was evaluated for the relationship between RRI and renal function. Results. Among 133 patients with resistant hypertension, 57.5% were male and the rest were female. Average age of participants and average RI were 48.26 ± 16.90 and 0.63 ± 0.80, respectively. There was no significant relationship between RI and gender (P > .05). Relationship between RI index with age, GFR, serum creatinine level, and albuminuria was significant in all cases (P < .05). Patients were divided into two groups with RI ≥ 0.7 and RI less than 0.7. Results showed a significant increase in serum creatinine and urinary albumin excretion in group with RI ≥ 0.7 (P < .05), while age, protein exertion level, and GFR in the two groups were not statistically significant (P > .05), despite the difference in the mean. Results of analysis of difference in the mean RI in 3 groups (macro-, micro-, normo- albuminuria) showed no significant difference between them (P > .05). Conclusion. These data demonstrate the clinical importance of renal Doppler that may be an effective way to evaluate the prognosis of renal involvement in resistant hypertension.